2015
DOI: 10.5901/mjss.2015.v6n4s2p632
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Employee Motivation and Job Performance: A Study at Universiti Teknologi MARA (Terengganu)

Abstract: Motivation is considered as a predictor of job performance. In other words

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The study also revealed that Gen Z teachers' work values positively affect their job motivation, job satisfaction, and performance. This finding supports the findings of Said, Zaidee, Zahari, Ali, & Salleh (2015) that job performance is positively correlated with job motivation and satisfaction. This implies that if school leaders and managers would employ strategies that cater to the work values of Gen Z teachers, it may result in increased motivation, satisfaction, and performance of the teachers.…”
Section: Discussionsupporting
confidence: 92%
“…The study also revealed that Gen Z teachers' work values positively affect their job motivation, job satisfaction, and performance. This finding supports the findings of Said, Zaidee, Zahari, Ali, & Salleh (2015) that job performance is positively correlated with job motivation and satisfaction. This implies that if school leaders and managers would employ strategies that cater to the work values of Gen Z teachers, it may result in increased motivation, satisfaction, and performance of the teachers.…”
Section: Discussionsupporting
confidence: 92%
“…The employees motivated at work have a large impact on the performance of enterprise. These results are also similar to some previous studies, based on which the motivation of employees has a positive impact on the performance of employees and organizational performance (Bao & Nizam, 2015;Said et al, 2015;Onanda, 2015).…”
Section: Model and Empirical Findingssupporting
confidence: 92%
“…The implication of this study suggested that a comfortable workplace environment helped to create a sense of belonging towards the organization, therefore encouraging the academic staff to be committed and perform well at work. The study by Said, Zaidee, Zahari, Ali, and Salleh (2015) focused on the relationship between three motivational predictors such as individual needs, personal preferences, and work environment on employee job performance. A total of 169 non-academic staff in Universiti Teknologi MARA (UiTM) Terengganu were selected randomly as the respondents to answer a questionnaire consisting of three different sections; (A) demographic questions, (B) dependent variable and (C) independent variables.…”
Section: Past Studiesmentioning
confidence: 99%